Determinación de Parásitos Intestinales en gallinas de traspatio en el Cantón Montalvo Provincia de Los Ríos - Briones Pelagallo, Angela del Pilar (2024)
Intestinal parasites are one of the main threats to the health and welfare of backyard chickens, causing significant economic losses in the poultry industry worldwide. Intestinal parasite infestation in backyard hens occurs through the proliferation of parasites that lodge in the intestinal tract of the host. The present work was carried out in Montalvo Canton, Los Rios Province, with the objective of determining the presence of intestinal parasite load in 75 backyard hens, which were obtained by random selection of 15 birds per family (5) that make up the commune, the procedure consisted of taking fecal samples for the performance of coproparasitic tests, therefore, they were performed in the laboratory of the Technical University of Babahoyo. In the experimental study work, the direct smear method was used, obtaining as a result the presence of intestinal parasites of 11%. The parasites found were Trichuri, with cases representing 37%, Larvae (13%), Protozoa (25%), Nematodes (25%), these results indicate the presence of parasitosis. Statistical analysis of the results led to the conclusion that the sex and age of the hens did not significantly influence the presence of intestinal parasites. During the visits to the different sectors, it was possible to identify that among the factors that put the health of the hens at risk were the lack of regular deworming programs, lack of adequate places, poor hygiene of the yards and feeders, and finally, the coexistence with other species endangers the health of the hens and increases the prevalence of parasitic infections.